A Placebo- and Midazolam-Controlled Phase I Single Ascending-Dose Study Evaluating the Safety, Pharmacokinetics, and Pharmacodynamics of Remimazolam (CNS 7056): Part II. Population Pharmacokinetic and Pharmacodynamic Modeling and Simulation - Wiltshire, Hugh R.; Kilpatrick, Gavin J.; Tilbrook, Gary S.; Borkett, Keith M. (Anesthesia and analgesia, 2012)
A new benzodiazepine, remimazolam, which is rapidly metabolized by tissue esterases to an inactive metabolite, has been developed to permit a fast onset, a short, predictable duration of sedative action, and a more rapid recovery profile than currently available drugs. We report on modeling of the data and simulations of dosage regimens for future study. A phase I, single-center, double-blind, placebo and active controlled, randomized, single-dose escalation study was conducted. Fifty-four healthy subjects in 9 groups received a single 1-minute IV infusion of remimazolam (0.01-0.3 mg/kg). There were 18 control subjects taking midazolam and 9 placebos. Population pharmacokinetic and pharmacodynamic modeling of the data was undertaken and the parameters obtained were used for Monte-Carlo simulations of alternative dosing regimens. A 4-compartment mammillary pharmacokinetic model of midazolam and a physiologically based recirculation model of remimazolam were fitted to the observed plasma levels. The recirculation model of remimazolam explained the observed high venous, compared with arterial, concentrations at later time points. The 2 models were used to simulate the arterial concentrations required for the pharmacodynamic models of sedation (Bispectral Index and Modified Observer's Assessment of Alertness/Sedation [MOAA/S]) and gave population mean pharmacodynamic parameters as follows: Bispectral Index-IC(50): 0.26, 0.07 μg/mL; γ: 1.6, 8.6; k(e0): 0.14, 0.053 min(-1); I(MAX): 39, 19, and MOAA/S-IC(50): 0.4, 0.08 μg/mL; γ: 1.4, 3.4; k(e0): 0.25, 0.050 min(-1) for remimazolam and midazolam, respectively. Simulations to obtain >70% of the population with MOAA/S scores of 2 to 4 were developed. This criterion was achieved (95% confidence intervals: 67%-74%) with a 6-mg initial loading dose of remimazolam followed by 3-mg maintenance doses at >2-minute intervals. Recovery to a MOAA/S score of 5 is predicted to be within 16 minutes for 89% (95% confidence intervals: 87%-91%) of the treated population after this loading/maintenance dose regimen. Population pharmacokinetic and pharmacodynamic models developed for remimazolam and midazolam fitted the observed data well. Simulations based on these models show that remimazolam delivers extremely rapid sedation, with maximal effect being reached within 3 minutes of the start of treatment. This property will enable maintenance doses to be given more accurately than with slower-acting drugs. No covariate effects considered to be clinically relevant were observed, suggesting that dosing by body weight may offer no advantage over fixed doses in terms of consistency of exposure to remimazolam within the weight range studied (65-90 kg).